2018
DOI: 10.22452/mojem.vol6no3.1
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Validating Model of Teacher Quality Using Structural Equation Modeling (Sem) Technique

Abstract: The main objective of this study is to establish Teacher Quality model (TQM). The study also aimed to identify the relationships between teacher quality (TQ) and students' academic performance (SAP). Furthermore, the study also seeks to verify the relationships among TQ dimensions. Structural Equation Modeling was used to test the model. A total of 450 teachers from secondary schools in Kwara state, Nigeria completed the survey. The analysis yielded four dimensions for Teacher Quality, namely Teacher Knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This includes improving the quality of teachers' teaching so that the objectives to be conveyed can be channeled more perfectly [2]. In previous study, it proved that the effectiveness of teacher pedagogy lies in their ability to produce excellent students in any field [3]. Meaning, the ability of teachers to process good pedagogy is the meeting point to teaching effectiveness and student excellence.…”
Section: Introductionmentioning
confidence: 99%
“…This includes improving the quality of teachers' teaching so that the objectives to be conveyed can be channeled more perfectly [2]. In previous study, it proved that the effectiveness of teacher pedagogy lies in their ability to produce excellent students in any field [3]. Meaning, the ability of teachers to process good pedagogy is the meeting point to teaching effectiveness and student excellence.…”
Section: Introductionmentioning
confidence: 99%
“…This quality relates to teachers' personal traits, which include the teachers' knowledge, abilities, and attitudes (Goh, 1996). Warrah et al (2018) stated that having good knowledge of the subject, effective communication skills, and behaviour in dealing with students are essential characteristics that improve the quality of a teacher's work. Their study revealed that students perform significantly better under teachers with good teaching knowledge rather than under teachers with inadequate subject knowledge.…”
Section: Teaching Qualitymentioning
confidence: 99%